Come hungry : salads, meals, and sweets for people who live to eat - Ben-Ishay, Melissa (William Morrow, an imprint of HarperCollinsPublishers, 2024)
"From Melissa Ben-Ishay-the co-founder of Baked by Melissa and creator of the viral Green Goddess Salad-comes an irresistible, veggie-packed cookbook with over 100 flavorful, nourishing recipes to inspire you to eat delicious meals that make you feel great." -- Publisher annotation.